Google rules : the history and future of copyright under the influence of Google - Gray, Joanne Elizabeth (New York, NY : Oxford University Press, 2020)
'Google Rules' traces the rise of Google through its legal, commercial and political negotiations over copyright. Today, Google reigns over an order that features empowered private companies and rapidly changing conditions. The book explores Google's accumulation of power over the past two decades and the implications for the public interest.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 7, 2020).
Keywords: Copyright; Copyright and electronic data processing; Google; Google (Firm) -- Influence; Authors and publishers -- Effect of technological innovations on